PELATIHAN PENILAIAN KINERJA PENDIDIK BAGI GURU DKI JAKARTA - Merry Lapasau; Soeparlan Kasyadi; Virgana Virgana (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
AbstrakDalam upaya mengembangkan diri sesuai tuntutan profesi guru, guru diharapkan dapat tetap menambah pengetahuan walaupun dalam keadaan keterbatasan seperti di masa wabah Covid-19 ini, antara lain dengan mengikuti seminar yang dilaksanakan secara daring. Oleh karena itu, kami tim abdimas dari universitas Indraprasta mengadakan seminar daring mengenai penilaian pendidik untuk para guru. Seminar dilakukan melalui media google meet sebagai bagian dari mematuhi protokol kesehatan di masa wabah Covid-19 dan dilaksanakan pada tanggal 10 Juni 2020. Seminar ini mengakomodasi guru-guru dari berbagai provinsi di Indonesia terutama dari DKI Jakarta. Kata kunci: Penilaian guru, seminar daring,  Covid-19 abstractTeachers are expected to be able to increase their knowledge in an effort to develop themselves according to the demands of the teaching profession even in limited circumstances such as during the Covid-19 outbreak. In order to keep up with the development in these days, they can attend online seminars. Therefore, we, the community service team from Indraprasta University, held an online seminar on teacher assessment for teachers. The seminar was conducted through google meet as a part of complying with health protocols during the Covid-19 outbreak and was held on June 10, 2020. This seminar accommodates teachers from various provinces in Indonesia, especially from DKI Jakarta. Keywords: Teacher assessment, online seminar, Covid-19Corresponding author: Merry Lapasau, E-Mail: mlapasau@gmail.com